A Monitoring System for Aquaponics Based on Internet of Things - Munirul Ula; Rizal Tjut Adek; Bustami Bustami; Syibbran Mulaesyi; Muhammad Bayu Juhri (LPPM Universitas Malikussaleh, 2022)
Finding suitable water sources for fish and plant cultivation appears to be difficult. In addition, land scarcity is decreasing agricultural productivity, so it is crucial to combine land and water conservation technology with various vegetable varieties for optimal yields. Aquaponics is a sustainable farming method that combines aquaculture and hydroponics. This water system must regularly circulate through the growing medium to provide the plants with nutrient-rich, filtered water. This research develops a smart aquaponics system that uses a mobile application accessible via the internet to control and monitor acidity, water level, water temperature, and fish nutrition. In this system, sensors are installed to collect data, which is then sent to the Ubuntu IoT Cloud server, which can be accessed in real time over the internet. So as to preserve the purity and circulation of water. In this study, the waterlevel sensor has a 100% measurement success rate, the pH sensor has a 93 % measurement success rate, and the temperature sensor has a 96% measurement success rate. The temperature and pH range of the pond water are optimal for aquaponics at 25 to 35 degrees Celsius and 6,5 to 7,5, respectively, and the aquaponics monitoring system is functioning properly. A suggestion for future research is the development of an aquaponic system that can be modified based on the type of plant and its nutritional requirements.